2002
DOI: 10.1046/j.1365-2664.2002.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the suitability of central European landscapes for the reintroduction of Eurasian lynx

Abstract: Summary1. After an absence of almost 100 years, the Eurasian lynx Lynx lynx is slowly recovering in Germany along the German-Czech border. Additionally, many reintroduction schemes have been discussed, albeit controversially, for various locations. We present a habitat suitability model for lynx in Germany as a basis for further management and conservation efforts aimed at recolonization and population development. 2. We developed a statistical habitat model using logistic regression to quantify the factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
176
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(183 citation statements)
references
References 66 publications
4
176
1
2
Order By: Relevance
“…Habitat models based on presence-absence data are the most standard approach to habitat modelling (e.g. Schadt et al, 2002b;Woolf et al, 2002;Naves et al, 2003;Seoane et al, 2003;Niedzialkowska et al, 2006). These models are often based on coarse-grained landscape and species information allowing coarse habitat inferences and predictions, but they may overlook biological details important for species conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Habitat models based on presence-absence data are the most standard approach to habitat modelling (e.g. Schadt et al, 2002b;Woolf et al, 2002;Naves et al, 2003;Seoane et al, 2003;Niedzialkowska et al, 2006). These models are often based on coarse-grained landscape and species information allowing coarse habitat inferences and predictions, but they may overlook biological details important for species conservation.…”
Section: Introductionmentioning
confidence: 99%
“…By quantifying species-environment relationships and prediction of species' geographic distributions from confirmed occurrences, they assume a direct link between the probability of presence and environmental suitability (Pearce & Ferrier 2001, Peterson 2006. Such models can be used to develop management decisions and conservation strategies (Schadt et al 2002, Barbosa et al 2003, Hirzel et al 2004, Russell et al 2004, among other practical and theoretical applications (see Peterson 2006 for a review). Their usefulness would be greatly strengthened if a relationship between local probability of occurrence and abundance were to exist.…”
Section: Introductionmentioning
confidence: 99%
“…In the empirical model, the strong explanatory power of the land-use type forest well reflects the biology of the Eurasian lynx which prefers forests of very large extends in mountainous areas (Schadt et al 2002;Basille et al 2008Basille et al , 2009. Basille et al (2009) showed that abundances of the lynx are closely related to prey density which was not available as a variable in our data set, but the nonlinear effect of the temperature variable might well indicate an optimum which beneficially affects productivity (Melis et al 2010) and therefore continuous resource availability.…”
Section: Discussionmentioning
confidence: 99%